Discontinuation of disease-modifying therapies in multiple sclerosis – Clinical outcome and prognostic factors. (August 2017) - Bsteh, Gabriel; Feige, Julia; Ehling, Rainer; Auer, Michael; Hegen, Harald; Di Pauli, Franziska; Deisenhammer, Florian; Reindl, Markus; Berger, Thomas
Background: Stable disease course may prompt consideration of disease-modifying treatment (DMT) discontinuation in relapsing–remitting multiple sclerosis (RRMS). Objective: To investigate the clinical outcome after DMT discontinuation and to identify predictive factors supporting decision-making. Methods: We included 221 RRMS patients, who discontinued DMT after ⩾12 months and had documented follow-up ⩾2 years after discontinuation. Hazard ratios (HRs) with 95% confidence intervals (CIs) regarding relapse and disability progression after DMT discontinuation were calculated from Cox regression models. Results: Age >45 years at discontinuation (HR = 0.47, CI = 0.23–0.95, p  = 0.038), absence of relapses for ⩾4 years on DMT before discontinuation (HR = 0.29, CI = 0.10–0.82, p  = 0.020) and absence of contrast enhancing lesions (HR = 0.46, CI = 0.28–0.78, p  = 0.004) were independent predictors of absence of relapse after discontinuation. Age >45 years and absence of relapses ⩾4 years on DMT combined had an HR of 0.06 (CI = 0.01–0.44, p  < 0.001). Higher Expanded Disability Status Scale (EDSS) at discontinuation, age >45 years and longer disease duration were significantly associated with disability progression after discontinuation. Conclusion: While freedom from further disease activity is generally unpredictable, there is a subset of patients (age ⩾45 years, DMT intake ⩾4 years without evidence of clinical or radiological disease activity) having a high likelihood of remaining relapse-free after DMT discontinuation. However, close clinical monitoring for recurrent disease activity is mandatory after discontinuing treatment.